2023
DOI: 10.1136/bmjhci-2023-100761
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of diabetes mellitus patients to use mHealth applications and its associated factors for self-care management in a low-income country: an input for digital health implementation

Abstract: BackgroundAlthough mHealth applications are becoming more widely available and used, there is no evidence about why people are willing to use them. Therefore, this study aimed to assess the willingness of patients with diabetes to use mHealth applications and associated factors for self-care management in Ethiopia.MethodsAn institutional cross-sectional study was conducted among 422 patients with diabetes. Data were collected using pretested interviewer-administered questionnaire. Epi Data V.4.6 for entering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This resonates with the worldwide trend of people using health apps to improve public health. With >55,000 health apps available globally on Google Store [ 15 ], these tools have, in some cases, been carefully evaluated to see how well they help with things such as diet [ 16 , 17 ], physical activity [ 18 ], or managing blood sugar [ 19 ]. mHealth apps are the most popular downloads from app stores.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with the worldwide trend of people using health apps to improve public health. With >55,000 health apps available globally on Google Store [ 15 ], these tools have, in some cases, been carefully evaluated to see how well they help with things such as diet [ 16 , 17 ], physical activity [ 18 ], or managing blood sugar [ 19 ]. mHealth apps are the most popular downloads from app stores.…”
Section: Discussionmentioning
confidence: 99%
“…Considering India’s socioeconomic background, the requirements for this population need to be assessed from various angles. It can be demonstrated by analyzing the findings of the study conducted by Walle et al [ 14 ] among 422 patients with diabetes in Ethiopia. The study aimed at understanding the willingness of patients with diabetes mellitus to use mHealth app and its associated factors for self-care management in a low-income country as a precursor to digital health implementation in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The study aimed at understanding the willingness of patients with diabetes mellitus to use mHealth app and its associated factors for self-care management in a low-income country as a precursor to digital health implementation in Ethiopia. The study concluded that the mHealth app developers should consider factors such as the patients’ age, place of residence, internet connectivity, attitude, perceived ease of use, and perceived usefulness while developing similar apps [ 14 ].…”
Section: Discussionmentioning
confidence: 99%